Business Model Improvement of PT Telin Submarine Cable Network to Become The World's Digital Hub - Winata, Hendra; Wandebori, Harimukti (The Indonesian Journal of Business Administration, 2014)
Abstract—. Nowadays, long-distance communication growth as an important part of human life, include data communication called internet. According to HCom (2011), 97% international data traffic carried by submarine cable network. Although this fact pointed that submarine cable network is the important infrastructure in telecommunication industry, unfortunately, TELIN did not optimize the strategic role of submarine cable network in its business model for reach its vision to become the world’s digital hub. Basically, this study using qualitative method where primary data comes from In-depth interview and focus group discussion with the expert of submarine cable within TELIN while secondary data comes from annual report and other publication data related to submarine cable industry. Some steps was taken to improve the business model of submarine cable network beginning with environment scanning summaries in SWOT Analysis, strategic positioning summaries in TOWS Matrix, and assess current business strategy and business model. Result of the study show that there are some key opportunities and strengths for TELIN to leverage international submarine cable network such as strategic geographical location of Indonesia and strong support from Indonesian Government combined with strong financial of TELKOM Group and broad coverage of domestic submarine cable network. Therefore, competitive business strategy of TELIN’s submarine cable network should be changed from cost-focus to integrated cost-leadership and differentiation. Along with that, business model also improved with value driven base where value proposition shifted from Focus in Serving Low-Cost International Bandwidth Requirement for TELKOM Group traffic while serving other International customer to Serving Low-Cost, High Quality, and Unique Service of Submarine Cable Network for Domestic and International Customer. For further study, this study can be as the inputs for adjust functional strategy in Marketing, Human Resources, Operation, and Financial aspect, which support the TELIN’s vision to become the world’s digital hub. Keywords: Business Strategy, Business Model, Submarine Cable, Digital Hub